The Challenge of Change: Planning for Social Urban Resilience. - Widborg, Anna (Springer Fachmedien, 2017)
Recent research has shown that the main challenge regarding urban resilience planning is to broaden the views and go beyond resilience in relation to climate change, and incorporate other important societal aspects. The aim of this chapter is therefore to analyse contemporary planning aims and practices relating to the adaptation and resilience of urban social change. How and to what extent is social change incorporated within the aims and practices of contemporary planning for urban resilience? What means are needed to bridge the gap between urban resilience planning for environmental and social change? The method used is a textual analysis of five case studies; three international and two Swedish studies, which results in a comparative and theme based analytical matrix. The main findings show that urban resilience is still dominated by its environmental change aspects, and that social urban resilience is not yet a commonly used phrase within contemporary urban planning. By adapting some of the approaches used within environmental urban resilience when planning for social changes however, cities can be more resilient and be able to better identify, adapt to and improve the changing social patterns such as demographic changes and social exclusion.
Keywords: Stadt; Resilienz; Transformation; Nachhaltigkeit; Stadtentwicklung; Planungsprozess; Anpassung; Klimawandel; Sozialverträglichkeit; Städtevergleich